Cardiac activity and evaluation - Burdick, J. A.; Adamson, J. D.; Chebib, F.; Koulack, D. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Thirty-eight paid male undergraduate volunteers participated in an experimental procedure structured around the viewing of 12 slides which were rated on a semantic differential rating scale. Heart rate (HR) and heart rate variability (HRV) were related to factor scores derived in principal component analysis of the ratings. In contrast to the results of a previous experiment relating cardiac activity to attitude, HRV was not found to be significantly associated with measures of evaluation but HR was.